The effects of pre-treatment with olibanum and its constituent, boswellic acid on synaptic plasticity impairments induced by lipopolysaccharide in rats - Narges Marefati; Farimah Beheshti; Sara Memarpour; Mohammad Rezaei; Seyed Mahmoud Hosseini (Mashhad University of Medical Sciences, 2021)
Objective: Olibanum (OLIB) and its component boswellic acid (BOSA) are suggested to have anti-inflammatory, anti-oxidant and neuroprotective effects. In the present work, we examined effect of OLIB, and BOSA on the synaptic plasticity impairment and oxidative stress indicators in a rat model of neuro-inflammation induced by lipopolysaccharide (LPS). Materials and Methods: Forty rats were divided into the following four groups: (1) Control, (2) LPS, (3) OLIB (200 mg/kg), and (4) BOSA (10 mg/kg). The animals were pre-treated with OLIB extract, BOSA or the vehicle 30 min before LPS (1 mg/kg) administration, for 6 days. On the 6th day, electrophysiological recording was done. Long-term potentiation (LTP) from CA1 area of hippocampus was assessed. The animals were then sacrificed and their brains were removed for evaluation of the levels of interleukin-6 (IL-6), nitric oxide (NO) metabolites, malondialdehyde (MDA), thiol, superoxide dismutase (SOD) and catalase (CAT) in the cortex. Results: Administration of LPS decreased amplitude (p <0.001) and slope (p <0.01) of field excitatory postsynaptic potential (fEPSP). Pre-treatment enhanced these parameters (p Conclusion: The results showed that OLIB and BOSA could improve synaptic plasticity impairment induced by LPS as shown by a decrease in an inflammation indicator along with the anti-oxidant effects.